2020
DOI: 10.1002/arch.21680
|View full text |Cite
|
Sign up to set email alerts
|

RNA interference‐mediated control of cigarette beetle, Lasioderma serricorne

Abstract: The cigarette beetle (CB; Lasioderma serricorne) is a pest on many stored products including tobacco. Fumigation is the common control method currently used. However, the options for controlling this pest are limited, due to resistance issues and phasing out of currently used chemical insecticides. Here, we evaluated RNA interference (RNAi) as a potential method for controlling the CB. RNA isolated from different stages was sequenced and assembled into a transcriptome. The CB RNA sequences showed the highest h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 48 publications
0
7
0
1
Order By: Relevance
“…According to statistics that many of the postharvest loss is caused by stored-product insects in the product during storage, such as red flour beetle (Tribolium castaneum), cigarette beetle (Lasioderma serricorne) and rice weevil (Sitophilus oryzae), they have spread widely, have an amazing capacity for reproduction, and have developed sophisticated feeding habits, making them global storage pests, threaten global grain security, and bringing great losses to human economic property. [1][2][3][4][5] Up to now, the major strategy of pest prevention and control is still synthetic chemical measures. [6][7] However, long-time use of synthetic chemicals inevitably brings environmental disturbance, pest resistance, possible harm to nontarge animals and threat to human health.…”
Section: Introductionmentioning
confidence: 99%
“…According to statistics that many of the postharvest loss is caused by stored-product insects in the product during storage, such as red flour beetle (Tribolium castaneum), cigarette beetle (Lasioderma serricorne) and rice weevil (Sitophilus oryzae), they have spread widely, have an amazing capacity for reproduction, and have developed sophisticated feeding habits, making them global storage pests, threaten global grain security, and bringing great losses to human economic property. [1][2][3][4][5] Up to now, the major strategy of pest prevention and control is still synthetic chemical measures. [6][7] However, long-time use of synthetic chemicals inevitably brings environmental disturbance, pest resistance, possible harm to nontarge animals and threat to human health.…”
Section: Introductionmentioning
confidence: 99%
“…A major challenge for the development of RNAi applications, however, is the identification of novel sensitive target genes, in particular in non-model organisms that often lack genomic data or laboratory colonies (Vogel et al, 2014). Some researchers take advantage of known RNAi-sensitive genes in model organisms and perform targeted gene mining strategies to verify the orthologous RNAi target in other insects (Pitino et al, 2011;Wang et al, 2011;Zhao et al, 2011;Zhu et al, 2011;Li et al, 2013;Rodrigues et al, 2017;Mogilicherla et al, 2018;Koo et al, 2020). Recently, a knowledgebased approach demonstrated that the spectrum of known lethal RNAi targets could be expanded by silencing genes that are functionally connected (Bingsohn et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that mRNA knockdown efficiency is not necessarily positively related to high mortality rates. Several uncontrollable factors can influence the RNAi response, like protein/mRNA half-life, gene function redundancy or the physiological importance of the targeted gene function (Schwinghammer et al, 2011;Li et al, 2013;Rinkevich and Scott, 2013;Bingsohn et al, 2017;Raje et al, 2018;Howell et al, 2020;Koo et al, 2020). Thus, we focused on organism-level analysis and did not consider gene expression as a key criterion for target selection.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, B. odoriphaga has developed increased resistance to insecticides because of heavy reliance on chemical insecticides ( Chen et al, 2017 ). To investigate insecticide resistance mechanisms and promote integrated pest management (IPM) strategies, researchers have studied several pests over the past few decades and achieved important progress in several areas, including genomics ( Xiao et al, 2021 ), transcriptomics ( Cheng et al, 2020 ; Nazar et al, 2020 ; Nor Muhammad et al, 2020 ; Wang et al, 2020 ; Fu et al, 2021 ; Zou et al, 2021 ), proteomics ( Prajapati et al, 2020 ; Chen et al, 2021 ), insecticide resistance ( Wang et al, 2020 ; Gong et al, 2021 ; Ullah et al, 2021 ), RNA interference ( Koo et al, 2020 ; Silver et al, 2021 ), and gene functions ( Yu et al, 2020 ; Li L. L. et al, 2021 ; Luo et al, 2021 ). However, further studies on the mechanism of insecticide resistance are required to clarify the genes directly involved in resistance and regulatory mechanisms associated with those genes.…”
Section: Introductionmentioning
confidence: 99%